Consumer Evaluation of Processing Variants of Pomegranate Juice - Anderson, Erika; Koppel, Kadri; Chambers, Edgar, IV (My University, 2014)
Increasing evidence of their health benefits has boosted the popularity of pomegranates. The effects of processing (e.g., pasteurization, drying) on pomegranate juice characteristics (e.g., color, phenolic content) and sensory attributes have been studied by several authors. The objectives of this study were to (1) understand if processing, such as pasteurization or drying, has an effect on pomegranate juice acceptance, and (2) if acceptance is related to healthy eating habits or variety seeking tendencies. Arils were removed from fresh Wonderful pomegranates for juicing or drying. Four treatments were prepared: fresh, fresh frozen, pasteurized, and reconstituted juice from dried arils. Fresh frozen, pasteurized, and reconstituted juices were evaluated by consumers for acceptance. Cluster analysis was conducted and four consumer clusters were found from evaluation of these juice treatments. Each juice was individually disliked by one of three clusters, demonstrating the effect of processing on acceptance. The fourth and largest cluster liked all three treatments. In addition, the consumers were asked to fill in Stage of Change and Variety Seeking scales. Liking scores were not found to be highly associated with healthy eating habits or variety seeking tendencies. This information is beneficial for the fruit processing industry, showing that processing can influence consumer acceptance.
Citation: Anderson, E., Koppel, K., & Iv, E. C. (2014). Consumer Evaluation of Processing Variants of Pomegranate Juice. Beverages, 1(1), 3–16. https://doi.org/10.3390/beverages1010003
Keywords: Consumer Acceptance; Flavor; Pomegranate Juice; Processing